AT

Bằng cách phối hợp nhiều phương pháp

x ²+5x-6

5x²+5xy-x-y

7x-6x²-2

CW
21 tháng 7 2016 lúc 19:05

x^2 + 5x -6

= x^2 + 5x  - (5+1)

= x^2 + 5x -5 -1

= 5(x-1) + (x^2 -1) 

= 5(x-1) + (x-1) (x+1)

= (5+x+1) (x-1)

5x^2 + 5xy -x-y

= 5x(x+y) - (x+y)

= (5x -1) (x+y)

7x - 6x^2 - 1             (câu này tớ tự ý sửa đề chút ^^!)

= 6x + x - 6x^2 -1

= 6x (1-x) - (1-x)

= (6x -1) (1-x)

Bình luận (0)
KL
21 tháng 7 2016 lúc 19:11

x2 + 5x - 6= x2 - x + 6x -6= x(x-1) + 6(x-1)= (x+6)(x-1)

5x+ 5xy - x - y= 5x2 - x + 5xy - y= x(5x-1) + y(5x - 1)= ( x +y)( 5x -1)

7x - 6x2 - 2= -6x+ 3x + 4x -2= -3x(2x - 1) + 2(2x -1)= (2 - 3x)(2x-1)

Bình luận (0)

Các câu hỏi tương tự
NV
Xem chi tiết
MQ
Xem chi tiết
VT
Xem chi tiết
NV
Xem chi tiết
H24
Xem chi tiết
LL
Xem chi tiết
NT
Xem chi tiết
NT
Xem chi tiết
DD
Xem chi tiết